Chaetocin Abrogates the Self-Renewal of Bladder Cancer Stem Cells via the Suppression of the KMT1A–GATA3–STAT3 Circuit - Yang, Zhao; Wang, Haifeng; Zhang, Nan; Xing, Tianying; Zhang, Wei; Wang, Guoqing; Li, Chong; Yu, Changyuan (Frontiers in Cell and Developmental Biology, 2020)
Bladder cancer stem cells (BCSCs) have the abilities of self-renewal, differentiation, metastasis, conferring drug resistance and exhibiting high tumorigenicity. We previously identified that KMT1A-GATA3-STAT3 axis drives the self-renewal of BCSCs. However, the therapeutic effect of targeting KMT1A in BCSCs remains unknown. In this study, we confirmed that the expression of KMT1A was remarkably higher in BCSCs (3~5 fold) than those in bladder cancer non-stem cells (BCNSCs) or normal bladder epithelial cells. Among the six KMT1A inhibitors, chaetocin significantly suppressed the cell propagation (inhibition ratio: 65%-88%, IC50= 24.4-32.5 nM), induced apoptosis (2-5 fold) and caused G1 phase cell cycle arrest (68.9% vs 55.5%) of bladder cancer (BC) cells, without influencing normal bladder epithelial cells. More importantly, chaetocin abrogated the self-renewal of BCSCs (inhibition ratio: 80.1%) via the suppression of KMT1A-GATA3-STAT3 circuit and other stemness-related pathways. Finally, intravesical instillation of chaetocin remarkably inhibited the growth of xenograft tumors (inhibition ratio: 71-82%) and prolonged the survival of tumor-bearing mice (70 days vs 53 days). In sum, chaetocin abrogated the stemness maintenance and tumor growth of BCSCs via the suppression of KMT1A-GATA3-STAT3 circuit. Chaetocin is an effective inhibitor targeting KMT1A in BCSCs, and could be a promising therapeutic strategy for BC.